Методи моніторингу людського сну з застосуванням оксиметрії та MEMS-датчиків - Андрєєв, К. О.; Герасименко, М. В. (ХНУРЕ, 2017)
Nowadays the sleep monitors play a crucial role in people lives since they make it possible to track sleep activity of individuals and therefore to foresee possible disasters or to keep things under control. Though precise monitors are expensive and they cannot be considered as wearable. The objective of this work is to make an overview of the methods that allow performing basic tracking of sleep activities and making it possible for the devices to be wearable.
Keywords: Методи моніторингу; Оксиметрія та MEMS-датчики